Exploring Religious Tourism Spots In Srinagar District Of Kashmir Valley – A Historical Study - Shabir Ahmad Lone; Dr. E. Ravi (CV. Radja Publika, 2026)
rinagar, the summer capital of Jammu and Kashmir, is often dubbed as the Venice of the East. Renowned through ancient times to the present, it has captivated travelers with its beauty. Serving as the backbone of Kashmir's economy, Srinagar attracts tourists from far and wide. While the district boasts numerous tourist spots, this document focuses solely on its religious sites, both renowned and lesser-known. The author's firsthand experiences shed light on Srinagar's significance as the nucleus of Kashmir's tourism industry.